Formação e profissionalização docente: análise do Programa Especial de Formação Pedagógica da UTFPR - Câmpus Medianeira - Remor, Clóvis Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is argued in this dissertation the limits and possibilities of special teacher training programs, stressed the concepts of training and certification. The reflection begins with the attempt to identify some characteristics of the content and how Brazil has sent its public policies on teachers to act in Basic Education, Vocational Training middle level and Technological Vocational Education. Scrolls through a long historical period, from 1827 to 2013, when the first and last overt concerns with the state teacher training. The substrate that supports the reflection lies in three analytical dimensions: first, the political dimension, which is explicit in the formulation of public policies and their consequences on the development of education law and, secondly, the theoretical dimension, which is reflected in the discussions of renowned authors and practical dimension, whose foundations are sought in field research by identifying the profile of teacher students of classes 15 and 16 and the didactic and pedagogical organization of the Special Program for Teacher Training - Profop - offered by the University Technology Federal of Parana - UTFPR - Campus Medianeira. The analysis of empirical material collected through questionnaires, is stretched between legal guidelines, practices developed in educational institutions and human development perspective. In this analysis we seek parity results for the analysis of related research on teacher students from special programs teacher training profile, so, in order, the socio-historical context and legal trajectory of this training, focusing the debate that arises in the political field and educational and existing tensions between the supply of special pedagogical training and the real need for qualified teachers to work in the classroom. Partial completion until then can be shown, is that, historically, the performance in the field of education is in an attractive alternative for...

Nesta pesquisa discutem-se os limites e as possibilidades dos programas especiais de formação pedagógica, tencionados pelas concepções de formação e certificação. A reflexão inicia com a tentativa de identificar algumas características do conteúdo e da forma como o Brasil tem encaminhado suas políticas públicas de formação de professores para atuação na Educação Básica, Educação Profissional Técnica de Nível Médio e Educação Profissional e Tecnológica. Percorre-se um longo período histórico, desde 1827 a 2013, quando são manifestas as primeiras e mais recentes preocupações do Estado com a formação docente. O substrato que sustenta a reflexão situa-se em três dimensões analíticas: por um lado, a dimensão política, que explicita-se na formulação de políticas públicas e seus desdobramentos na elaboração da legislação educacional e, por outro, a dimensão teórica, que se espelha nas discussões de autores renomados e a dimensão prática, cujos fundamentos são buscados na pesquisa de campo a partir da identificação do perfil dos cursistas de turmas 15 e 16 e da organização didático-pedagógica do Programa Especial de Formação Pedagógica - Profop - ofertado pela Universidade Tecnológica Federal do Paraná - UTFPR - Câmpus Medianeira. A análise do material empírico, coletado por meio da aplicação de questionário, é tencionada entre orientações legais, práticas desenvolvidas nas instituições formadoras e perspectiva de formação humana. Nessa análise, busca-se paridade de resultados pela análise de pesquisas correlatas acerca do perfil de cursistas de programas especiais de formação pedagógica, para, em fim, contextualizar a trajetória sócio-histórica e legal dessa formação, focalizar o debate que se coloca no campo político e educacional e os embates existentes entre a oferta de formação especial pedagógica e a real necessidade de professores habilitados...
Keywords: Professores - Formação; Ensino fundamental; Ensino profissional; Universidades e faculdades; Teachers, Training of